Development of a transformation system for sugarcane (Saccharum spp. hybrids) in South Africa using herbicide resistance as a model system - Snyman, Sandra Jane (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.